Alprazolam withdrawal and tolerance measured in the social conflict test in mice - Votava, M; Krsiak, M; Podhorná, J; Miczek, K A (Psychopharmacology, 2001)
RATIONALE: It is difficult to assess withdrawal from benzodiazepines, and preclinical assessment of behaviour during social conflict offers the opportunity to quantify tolerance and withdrawal by measuring aggressive, defensive and social behaviour. The relationship between benzodiazepine withdrawal symptoms and the development of tolerance is not well understood. Are withdrawal symptoms dependent on the development of tolerance? OBJECTIVE: The aim of the present study was to compare the development of tolerance to alprazolam effects on the behavioural repertoire during the social conflict test in mice, and to determine whether or not behavioural changes during alprazolam withdrawal are correlated with the development of tolerance. METHODS: An experimental model consisting of interactions of pairs of singly housed male mice with non-aggressive group-housed male mice was used. Alprazolam (1 mg/kg) was given orally once or repeatedly (twice daily) for 8 or 21 days. Behaviour was measured, based on videoanalysis, in aggressive mice before treatment, 30 min or 3 days after the last dose, respectively. RESULTS: A single administration of alprazolam significantly reduced aggressive activities and increased social investigation without changing locomotion or other behaviour. Tolerance developed to the inhibitory effects of alprazolam on aggressive behaviour but not to the effects of alprazolam to increase social investigation. When withdrawn from alprazolam, mice exhibited less social investigation and locomotion while aggression tended to be increased. CONCLUSIONS: Tolerance to the alprazolam effects on aggressive and social behaviour developed at different rates suggesting that they are differentially regulated. Furthermore, the evidence of withdrawal responses appearing in a behaviour to which tolerance had not developed does suggest that tolerance and withdrawal phenomena are dissociated in benzodiazepines.
Keywords: anxiolytika; myši; konflikt (psychologie); mužské pohlaví; Locomotion; Male; Alprazolam; Anti-Anxiety Agents; sociální chování; Mice, Inbred ICR; Conflict, Psychological; Drug Tolerance; lokomoce; Animals; Social Behavior; Mice; zvířata; tolerance léku; chování zvířat; alprazolam; abstinenční syndrom; myši inbrední ICR; Behavior, Animal; Substance Withdrawal Syndrome